REMOTE PATIENT MONITORING WITH WEARABLE DEVICES AND MOBILE HEALTH SYSTEMS FOR CHRONIC DISEASES: CLINICAL EFFECTIVENESS, CHALLENGES, AND FUTURE PROSPECTS – A REVIEW - Manicka, Martyna; Baranowicz, Michał; Mazurkiewicz, Weronika; Borecka, Zuzanna; Sobczak, Agnieszka; Szymczak, Alicja; Jaworowicz, Anna; Piasecka, Joanna; Gołembiewski, Bartosz; Mulski, Grzegorz (International Journal of Innovative Technologies in Social Science, 2026)
Background: The rapid advancement of technology makes it possible to achieve improvements in medical services and patient adherence. It also enables the early detection of disease exacerbations and improves the management of chronic conditions outside the clinical setting. Digital health tools such as wearable sensors and mobile applications can enhance patients’ perceived competence.Objectives: This aim of this review was to analyze the available scientific data on the use of remote monitoring (via wearables devices and mobile healthcare systems) in patients with chronic diseases. The analysis focused on their effectiveness, safety, and practical potential.Methods: A literature review on remote monitoring of patients with chronic diseases was conducted using the PubMed, Embase and Medline databases for publications in English language from 2015 to 2026. The analysis included clinical trials, metanalyses, studies validating remote monitoring devices, and guidelines issued by scientific societies. The selection of studies was based on predefined inclusion and exclusion criteria. The results were presented as a qualitative analysis.Conclusions: Remote patient monitoring and digital interventions, combined with active clinical support, improve blood pressure control, exercise capacity, therapy engagement, and adherence, and reduce hospitalizations for cardiovascular disease. In respiratory diseases, RPM technology provides accurate vital sign measurements, although it does not always lead to better clinical outcomes. In type 2 diabetes, comprehensive digital interventions support glycemic control and healthy behaviors, while in neurological rehabilitation, wearable systems and machine learning-based applications improve limbs motor function. Despite the advantages and demonstrated effectiveness of remote patient monitoring (RPM) and wearable device–based interventions, technological complexity and limited digital literacy are significant implementation barriers that may limit long-term engagement.